Cyclic behavior of moment-resisting frames strengthened with steel curved dampers. (November 2019) - Hsu, H L; Halim, H
Abstract: Steel moment frames have been widely used for earthquake-resistant purposes. These systems possess significant ductility, however, excessive deformation due to the lower structural stiffness. In order to improve the behavior of moment-resisting frames when subjected to cyclic loads, a new design that combined steel curved damper and brace member was proposed in this study. The curved damper was cut from steel plate and was placed in the center portion of the brace member. The new device was attached to the frame and was used to dissipate energy throughout the load application. A series of loading tests on steel frames strengthened with the proposed design were carried out. The strength and energy dissipation capabilities of frames with and without the strengthening device were compared. It was found from the comparisons that the behavior of framed structures was significantly improved, thus justified the effectiveness of the proposed design.